Bilateral Retinal Angiomatous Proliferation in a Variant of Retinitis Pigmentosa - G. Aloe; C. M. De Sanctis; C. Strafella; R. Cascella; F. Missiroli; M. Cesareo; E. Giardina; F. Ricci (Case Reports in Ophthalmological Medicine)
Purpose. To describe the first case of bilateral retinal angiomatous proliferation (RAP) in a patient with a variant of retinitis pigmentosa (RP). Case Report. An 85-year-old man with RP presented with visual acuity decrease and metamorphopsia in the left eye (LE). Fundus examination revealed typical signs of RP in both eyes, associated with intraretinal macular hemorrhage in the LE. Multimodal imaging, using Colour fundus Photography, Fluorescein (FA), and Indocyanine Green Angiography (ICGA) as well as Spectral-Domain Optical Coherence Tomography (SD-OCT) and Optical Coherence Tomography Angiography (OCTA), revealed a type 3 neovascular lesion in the involved eye. Genetic testing (NGS analysis) was performed to search for genetic variants correlated with the disease phenotype displayed by the patient. The patient was treated with intravitreal injections of bevacizumab, according to a fixed protocol of bimonthly injections plus a booster dose at second month. After 9 months, he was referred for visual acuity decrease and metamorphopsia in the fellow eye, where SD-OCT/OCTA showed a type 3 neovascular lesion in the right eye (RE). He was scheduled for intravitreal injections of bevacizumab. In both eyes, treatment with intravitreal bevacizumab was successful.